PENGARUH MINAT BACA TERHADAP PRESTASI BELAJAR MAHASISWA PGSD PADA MATA KULIAH PENGANTAR PENDIDIKAN - Zakiyah Ismuwardani; Intan Aliantan (Institut Pendidikan dan Bahasa Invada, 2020)
This study aims to determine the effect of reading interest on the learning achievement of PGSD students in the Introduction to Education course. The research method used is a quantitative approach method. The population in this study were PGSD students. The sampling technique of the study used a sampling technique. Data was collected by means of a questionnaire. The main instrument in this study was a questionnaire on reading interest and learning achievement. The results showed that the students who became the object of this research based on data analysis showed that by calculating Rcount, a value of 0.981 was obtained, then the value was compared with Rtable at a significant level of 5%, namely 0.432, indicating that Rcount > Rtable, so the hypothesis (H0) was rejected and (H1) is accepted. So it can be concluded that there is an influence between reading interest on the learning achievement of PGSD students in introductory education courses.